Where Does the Market Come From? Why the Controversy Between Polanyi's "Substantivists" and "Formalist" Neoclassical Protagonists of a Universal Market Was Never Solved" - Heinsohn, Gunnar (Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy, 2008)
In Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy - Metropolis-Verlag, 2008.
Keywords: formalist; substantivist

Third Sector, Social Economy, Civil and Solidarity-Based Economy: European Reality and Theoretical Debate | - Laville, Jean-Louis (2008)
This is a book chapter from: The Social Generative Action of the Third Sector – Comparing International Experiences Edited by H. K. Anheier; G. Rossi, L. Boccacin, 2008, Vita e Pensiero, Milano
Keywords: social economy; solidarity economy